Insights on the Biomarker Identification for Chronic Gastritis with TCM Damp Phlegm Pattern [Letter] - Hu J; Liu X; Yao P (Journal of Inflammation Research, 2024)
Jian Hu,1,2,* Xiaoyun Liu,1,2,* Peng Yao1,2 1First Teaching Hospital of Tianjin University of Traditional Chinese Medicine, Tianjin, People’s Republic of China; 2National Clinical Research Center for Chinese Medicine Acupuncture and Moxibustion, Tianjin, People’s Republic of China*These authors contributed equally to this workCorrespondence: Peng Yao, First Teaching Hospital of Tianjin University of Traditional Chinese Medicine/National Clinical Research Center for Chinese Medicine Acupuncture and Moxibustion, Tianjin, 150006, People’s Republic of China, Email 75232745@qq.com